Form and Function of Carrying Tools in Traditional and Contemporary Culture - Hendriana Werdhaningsih (ITB Journal Publisher, LPPM ITB, 2009)
The Javanese Traditional Carrying Tools are categorized into two kinds based used of materials: anyaman made of woven bamboo or rattan and the other was made of cloth. The Traditional Javanese Carrying Tools that were made of bamboo/ rattan is actually a kind of container with different shapes. The types of goods that were brought was related to the shapes of the containers, demonstrate the type of interactions between the carrier and the goods. The Traditional Carrying Tools made of cloth have the flexibility in terms of being the containers of the carried goods. Selendang is used to carry goods, including the bamboo/ rattan containers and to carry babies. It can be used rumpled and straightened depends on the technical needs of carrying tools preferred by the user. In contemporary culture, the form and design of carrying tools more less construct by fashion and trends besides those practical used. Some product are being 'classic', some other are being 'fad'. Both products, traditional and contemporary have their own style, uniqueness, and own context. Analyzing both in design point of view is important as evaluation process, to finding new problems that will be starting point to create new products. Indonesia is well known for its abundant richness in traditions, which include the culture, the art, and the traditional products. Such treasure of traditions can inspire the development and invention of various kinds of artwork and current products.